Reproducibility of Optic Nerve Head Hemoglobin Measures. Issue 4 (April 2016) - Mendez-Hernandez, Carmen; Garcia-Feijoo, Julian; Arribas-Pardo, Paula; Saenz-Frances, Federico; Rodriguez-Uña, Ignacio; Fernandez-Perez, Cristina; de la Rosa, Manuel Gonzalez
Abstract : Purpose: To evaluate intraobserver, interobserver, within-session and between-session reproducibility of the measurement of optic nerve head (ONH) hemoglobin levels by color analysis using Laguna ONhE [optic nerve hemoglobin (ONH Hb)] program. Materials and Methods: This was an observational prospective study of 29 eyes (11 glaucomatous; 18 healthy eyes). Two examiners obtained 2 retinal photographs (Canon non-mydriatic retinal camera CD-DGi, Canon Inc., Tokyo, Japan) in 2 testing sessions 3 weeks apart and analyzed the images using Laguna ONhE. The following parameters were quantified: ONH hemoglobin amounts across the whole disc (ONH Hb) and in the vertical disc diameter (8&20 Hb), cup-disc ratio (C/D), and the Glaucoma Discriminant Function (GDF). Agreement was illustrated using the Bland-Altman plots and reproducibility was assessed comparing the intraclass correlation coefficients (ICC). Results: In session 1, examiner 1 found mean levels of ONH hemoglobin of 67.94±8.70% in healthy eyes and of 57.90±5.36% in glaucomatous eyes. Corresponding values for examiner 2 were 68.27±8.52% and 57.83±4.88%, respectively. ONH Hb and 8&20 Hb measurements were lower in glaucomatous eyes ( P =0.002 and P =0.001 respectively). GDF was also more pathologic in glaucomatous group. C/D ratio estimation was greater in the glaucoma group ( P =0.003). ONH Hb and 8&20 Hb showed the highest ICCs (all above 0.9). Variability was greater for GDF (ICC>0.8) and C/D ratio estimation (ICC>0.71). Conclusions: Measurement of ONH Hb levels using the Laguna ONhE program shows high reproducibility both in glaucomatous and nonglaucomatous ONHs.